Estudio de diferentes agentes osmóticos en la transferencia de masa y vida útil en el babaco deshidratado - Hidalgo, N. (2009)
In the present investigation were studied the effects on mass transfer and shell life of dried babaco previously treated with different osmotic agents. The experiments served to establish the highest drying rate, extended shell life, the best physical and sensory characteristics of Babaco dehydrated with four different osmotic agents (sucrose, honey, glucose and a mixture of honey with sucrose). Resulting in the solution subjected to Babaco honey - sucrose was the best values